Evaluation of Delay Characteristics at A 4- Legged Signalised Intersection for Improvement in The Level of Service. A Case Study of Jinja Road Intersection. - Babirye, Joanitor (Kabale University, 2023)
Intersections are a critical aspect of street design as the point where motorist, bicycle, and pedestrian movements converge. Successful intersection design addresses all mobility and safety goals as well as opportunities to enhance the public realm. This section explores intersection design and operation, from signal timing to crosswalk, and investigates each concept as it relates to citywide goals for safety, mobility, and more vibrant, accessible public spaces. Their strength lies in their ability to reduce the number of vehicular conflicts at places where the roads meet and thereby enhance intersection capacity and safety. There are additional intangible benefits such as their traffic calming effect, guiding vehicles to their respective directions and aesthetics. Increasingly, many intersections in growing urban towns i.e., Kampala city are becoming problematic due to capacity challenges resulting from rapid traffic growth. Hence a micro- simulation model such as VISSIM was used to assess the performance, level of service of Jinja road intersection in order to minimize the uncertainties of increased; control delays, queue lengths experienced during peak hours. The aim of this study investigated the viability of using micro- simulation model such as VISSIM in evaluation of operational performance, improved capacity, reduced delays and queue lengths of Jinja road intersection as a case study. Field traffic volume studies for the entire intersection approaches were performed; Delay studies for the subject approach (Jinja road approach) were also undertaken. Geometric data as well as data from the field studies were used to calibrate a model for the existing situation. The VISSIM model is an advanced micro- simulation tool with capabilities of modelling both intersection and traffic signals to acceptable level of detail. the model’s ability is to capture the effects of various geometric and traffic features like number of lanes, position of the stop line and proportion of turning flows, and evaluates their impacts on the resulting capacities and delay. Motion of an individual vehicle is simulated in small time steps and each vehicle is followed from the time it is generated into the network to the point of its exit. Vehicular behaviour at the intersection is modelled on the basis of a gap acceptance approach. Capacity, delay, queue length and degree of saturation were observed from the model where signalization simulation options for existing signalized and improved model were determined. The results indicated that the improved signalization model produced the better parameter results as compared to the existing model. However, there is an increase in the queue length and delay as well as a decrease in capacity on Jinja road approach attributed to alteration in the balance of traffic flow due to the signalization on all the approaches. Generally, there is a slight improvement in the flow of traffic after improvement however that the level of service is still low i.e., LOS F and degree of saturation is still high (greater than 1.00). This could be attributed to the fact that the total Pcus from all the approaches exceed 10000 Pcus/hr which necessitates grade separation. Grade- separation is one of the alternatives in solving congestion at Jinja road intersection, but it is very expensive to implement.